CHARACTERISTICS OF RUMEN FERMENTATION WITH FEED FORMULATION USING MOLASSES IN-VITRO - Sari, Y. M.; Mega Sari, Rica; Nurhaita, Nurhaita; Surtina, Dara; Astuti, Tri (Journal of Animal Nutrition and Production Science, 2024)
This study aims to determine the effect of molasses use in ruminant livestock rations on rumen fluid characteristics in vitro. This study was conducted using a Completely Randomized Design experimental method with 3 treatments and 5 replications, the treatments consisted of: P0 = Ration formulation without molasses use, P1 = Ration formulation with 3% molasses use, P2 = Ration formulation with 6% molasses use. The variables observed were pH value, NH3 production and rumen fluid VFA production. The results of the study for pH value obtained P0 = 6.98; P1 = 6.94; P2 = 6.89. NH3 production P0 = 10.02 mg / 100ml; P1 = 10.89 mg / 100ml; P2 = 11.42 mg / 100ml and VFA production P0 = 104.00 mM; P1 = 120.00 mM; P2 = 130.00 mM. Based on the results of the study, it was shown that the use of molasses in the ruminant livestock ration formula had no significant effect (P>0.05) on the pH, and had a significant effect (P<0.05) on the production of NH3 and VFA in the rumen in vitro. Where the use of molasses up to 6% in the ration formulation can increase NH3 production, VFA production and maintain the pH value of the rumen fluid.